PENGARUH HARGA TERHADAP USAHA MENINGKATKAN VOLUME PENJUALAN MOBIL XENIA PADA PT. ASTRA DAIHATSU Tbk CABANG MALALAYANG MANADO - Christian Almendo Benaino; Johny R. E. Tampi; Tinneke M. Tumbel (JURNAL ADMINISTRASI BISNIS, 2017)
The existence of competition between automotive products between companies impact on the determination of competitive prices and affordable by consumers to encourage increased sales volume. Thus, this study aims "to determine the effect of price on car sales volume Xenia at PT. Astra Daihatsu Tbk Malalayang Branch of Manado City ". This research uses descriptive method with quantitative approach, then applied percentage analysis and for hypothesis testing applied simple linear regression analysis technique and product moment correlation The results of this study indicate that (1) the price level of Xenia cars varies according to the type and size / model of the vehicle, then each year increases the price by an average of 4.9%, while the sales volume decreases from year to year. The decline in the level of sales volume, in addition influenced by factors of price increases, is also caused by the replacement of vehicle type. (2). The result of hypothesis test shows that between price and sales volume have relationship relation and influence that its contribute and very significant, but negative linear pattern. This means that if the price is raised to a certain level, it will result in a decrease in sales volume of Xenia Cars. Keywords: Price, Sales Volume, Xenia car